Maantar Jujuran Tradition in Banjarese: Increasing Social Status or Maintaining Values - Rahmatullah, Prayudi (Sharia and Law Faculty, 2023)
In the Banjarese culture of South Kalimantan, there are a number of ancient wedding traditions that are still practiced today. One of these is the maantar jujuran, which is used to determine whether or not a marriage will be successful. The purpose of this study is to examine the maantar jujuran tradition of Banjares marriage in South Kalimantan through the lens of Peter L. Berger's social constructionist theory. This study employed a descriptive quantitative methodology with phenomenological analysis of the Banjar community in South Kalimantan. Methods for compiling data from many sources of literature relevant to research. The results of this study show that traditional Banjarese marriages have been conducted in a manner similar to the heritage that constitutes the nenek moyang warisan. According to social constructionist theory, interactions between members of different communities regarding rural justice traditions have been going on for quite some time in this study. Many people still practice this tradition because they believe in its inherent goodness. Additionally, it is known that one of the goals of the Banjar people in carrying out this tradition is to elevate their social standing within the community. It is hoped that this study would contribute to the growth of knowledge, particularly in the field of family law; given that Indonesia has such a wide variety of cultural norms when it comes to conducting marriage ceremonies, this topic is particularly interesting from a sociological, cultural, political, and other vantage points. Dalam budaya Banjar Kalimantan Selatan, ada beberapa tradisi pernikahan kuno yang masih dilakukan hingga saat ini. Salah satunya adalah maantar jujuran, yang digunakan untuk menentukan berhasil atau tidaknya suatu perkawinan. Tujuan dari penelitian ini adalah untuk mengkaji tradisi maantar jujuran perkawinan Banjar di Kalimantan Selatan melalui teori konstruksi sosial Peter L. Berger. Penelitian ini menggunakan metodologi deskriptif kuantitatif dengan analisis fenomenologi masyarakat Banjar di Kalimantan Selatan. Metode pengumpulan data dari berbagai sumber literatur yang relevan dengan penelitian. Hasil penelitian ini menunjukkan bahwa perkawinan adat Banjar telah dilakukan dengan cara yang mirip dengan warisan leluhur nenek moyang. Menurut teori konstruksi sosial, interaksi antara anggota komunitas yang berbeda mengenai tradisi peradilan pedesaan telah berlangsung cukup lama dalam penelitian ini. Banyak orang masih mempraktekkan tradisi ini karena percaya akan kebaikan yang terkandung di dalamnya. Selain itu, diketahui bahwa salah satu tujuan masyarakat Banjar dalam menjalankan tradisi ini adalah untuk mengangkat derajat sosial mereka di tengah masyarakat. Diharapkan penelitian ini dapat memberikan kontribusi bagi pertumbuhan ilmu pengetahuan, khususnya di bidang hukum keluarga; Mengingat bahwa Indonesia memiliki norma budaya yang begitu beragam dalam pelaksanaan upacara perkawinan, topik ini sangat menarik dari sudut pandang sosiologis, budaya, politik, dan lainnya.